Inferior long-term results of a randomized controlled trial initially demonstrating enhanced sensory nerve recovery using a chitosan nerve tube - Aman, Martin; Preisner, Fabian; Mayrhofer-Schmid, Maximilian; Eisa, Amr; Schwarz, Daniel; Kneser, Ulrich; Harhaus-Wähner, Leila; Böcker, Arne Hendrik (Plastic and reconstructive surgery, 2025)
Background: Traumatic peripheral nerve injuries can result in significant functional impairments and long-term sequelae. This study evaluated the long-term outcomes of a chitosan tube implant to protect epineural coaptation after peripheral nerve injuries using 2 different tube versions (different wall thicknesses and resorption characteristics), compared with a control group. The study focused on pain levels, sensory function, and overall functional outcomes. Methods: Patients who received a tube implant around direct coaptation sites of digital nerves were randomized and compared with control patients with no additional tube protection. Pain levels, sensory function, grip force, and functional scores were assessed at time points ranging from 3 months to 5 years postoperatively. Tube biodegradation was measured using high-resolution magnetic resonance neurography and categorized. Results: Patients with the first tube version had higher pain levels compared with the control group after 5 years, and reported more symptoms of numbness and hypersensitivity. Patients with the second version exhibited higher pain levels at 3 months that did not persist at 6 months, but they showed compromised sensory function, with higher 2-point discrimination values compared with the first and control groups. No differences were found in grip force or functional scores between the groups. Magnetic resonance imaging displayed remnants of implants even at long-term follow-up. Conclusions: The findings suggest potential limitations attributable to increased pain and impaired sensory function associated with tube implantation in the long term. In the short term, however, the material seemed to have a protective effect (as published previously). The resorption process was not complete at the end of the 5-year observation period. This might explain the prolonged scarring and inferior long-term results. Future research should focus on improving tube materials and design to minimize adverse effects and enhance functional outcomes.
Gesehen am 18.07.2025